Crusading and Ideas of the Holy Land in Medieval Britain - Hurlock, Kathryn; Whatley, Laura J. (Brepols, 2022)
Crusading and western interaction with the Holy Land is often a contentious topic, not least because modern popular perception of medieval east-west contact is that it was defined by violence, conquest, and religious persecution. Building on recent scholarship, this collection of essays takes an interdisciplinary approach to the role of crusading and contact with the Holy Land in medieval Britain in order to investigate the myriad ways in which these contacts influenced artistic, literary, visual, and social culture in medieval Britain. By looking at new material and focusing on the domestic response to crusading and the Holy Land, the contributions gathered here offer new insights into the influence of these contacts on the medieval British world view, as well as their impact on topics such as ideals about masculinity and kingship, geographical perception, and aspirational codes of conduct for the medieval British elite.